Decentralisation, Privatisation and Changes in the Financing of Education in Slovenia: Greater Opportunities for Citizens? - Stanka Setnikar Cankar (Central European Public Administration Review)
This paper has been conducted to explore the major issues and problems in higher education regarding the decentralisation, privatization, accreditation and public financing processes in Slovenia. There is significant political pressure supporting the idea that if Slovenia has regions they should be as busy as possible. The real danger is that the introduction of small regions and 7-10 universities will only strengthen centralisation. Slovenian public expenditure on education has generally been relatively high. However, in recent years the proportion of annual GDP spent on higher education has decreased. There is a need for student protection and regulation. For many public and private universities, however, accreditation is mainly seen as an opportunity to strengthen their image by demonstrating their quality.